EMPLOYEE ENGAGEMENT AS A STRATEGIC ASSET IN FOUR-STAR HOTELS: EMPIRICAL EVIDENCE FROM BATAM CITY - Siti Rohani; Viona Agustin; Muhammad Donal Mon (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study examines the factors influencing employee engagement in four-star hotels in Batam City. The main focus is on motivation, commitment, training, and compensation received by employees.METHODOLOGY - Using a quantitative approach, data were collected through questionnaires distributed across various hotel departments. The results indicate that motivation, commitment, training, and compensation have a positive and significant effect on employee engagement. In addition, motivation is proven to mediate the relationship between these variables and employee engagement.FINDING - These findings are expected to provide input for hotel management to pay greater attention to employee development, reward systems, and the creation of a supportive work environment to enhance employee retention and productivity. This study also demonstrates that employee engagement is not only important for individual performance but also for overall organizational progress.